Contribution of Integrated Farming System (IFS) Units towards Household Income in Kerala - Chandran, Vani; Saurav, Subhash Kumar; Chakravarty, Ritu; Kalla Ashok (Indian Journal of Extension Education, 2023)
From an economic point of view, combining various components in the same unit helps to diversify farmers’ income. An attempt was made to determine the contribution of various components, adopted in an IFS unit, to the annual household income among the IFS units of Kerala during 2022. In this study, total annual household income was computed by summing up the gross income from all the on-farm sources. The study revealed that 52.78% of respondents were found in the low-income category, followed by one-third in the medium-income category. Among the selected components, the contribution of income from the crop component, dairy component, and poultry component, was found to be low to medium, while the trend in income generation from fish component was from medium to low. In the case of apiculture and mushroom components, medium to high-income generation was also noticed. It was also found that farm size, experience in farming, economic motivation, training undergone, and herd size were positively correlated with the total farm income of households.